Metode Pembelajaran Calistung Melalui Teknis Bermain - Suyanti, Herma Suyanti; Shalahudin, Shalahudin; Riyanti, Ida (Center for Religious Studies and Social Empowerment Foundation, 2022)
This research focuses on the application of the Calistung learning method in improving the language development of Early Childhood 5-6 years in RA Al-Annur Permata, Eka Jaya Village, Palmerah District, Jambi City. The main problem of this research is why the method of reading, writing, counting (Calistung) at RA Al-Annur Permata Jambi City in improving early childhood language development at RA Al-Annur Permata Jambi City is not optimal, with indicators not yet creative teachers in carrying out the learning process . This research is a descriptive qualitative research with a purposive sampling technique approach. The research findings show that RA Al-Annur Permata has applied several Calistung methods in his learning. The application of Calistung learning through play for children is indeed very necessary in addition to making interesting learning not monotonous, media learning also makes it easier for children to understand because it uses concrete concepts. RA's Calistung method. Al-Annur Permata media has an important role in conveying learning to children. The obstacle to implementing Calistung learning for early childhood in Class B RA Al-Annur Permata is the limited competence of the teacher and the inadequate APE and not appropriate for the child's age. Penelitian ini berfokus pada penerapan metode pembelajaran Calistung dalam meningkatkan perkembangan berbahasa Anak Usia Dini 5–6 tahun di RA Al-Annur Permata Kelurahan Eka Jaya Kecamatan Palmerah Kota Jambi. Masalah utama penelitian ini adalah mengapa Metode membaca, menulis, menghitung (Calistung) di RA Al-Annur Permata Kota Jambi dalam peningkatan perkembangan bahasa anak usia dini di RA Al-Annur Permata Kota Jambi belum optimal, dengan indikator belum kreatifnya guru dalam melaksanakan proses pembelajaran. Penelitian ini merupakan penelitian kualitatif diskriptif dengan pendekatan teknik purposive sampling. Temuan penelitian menunjukkan bahwa RA Al-Annur Permata telah menerapkan beberapa metode Calistung dalam pembelajarannya. Penerapan pembelajaran Calistung melalui bermain bagi anak memang sangat diperlukan selain membuat pembelajaran menarik tidak monoton pembelajaran media juga membuat anak lebih mudah mengerti karena menggunakan konsep yang konkret. Metode Calistung yang dijalankan RA. Al-Annur Permata media mempunyai peran penting dalam menyampaikan pembelajaran kepada anak. Kendala penerapan pembelajaran Calistung anak usia dini di Kelas B RA Al-Annur Permata adalah kompetensi guru yang terbatas dan APE-nya yang kurang memadai serta tidak sesuai dengan usia anak.